Source-Based Writing as a Way to Language Acquisition - SIZOVA, Yulia; BLAGONRAVOVA, Marina (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this study was to demonstrate that teaching writing elements based on authentic written sources can be beneficial throughout a Master English course. Paraphrasing and patching are necessary stages in the development of the ability to express your own ideas; Furthermore, adopting a strategy of using a certain amount of plagiarism can be successful in improving the knowledge of a foreign language. Study participants were 111 students who completed their master’s courses at 3 leading universities in Moscow, Russia. RESUMEN El propósito de este estudio fue demostrar que enseñar elementos de la escritura sobre la base de fuentes auténticas escritas, puede resultar beneficioso a lo largo de un curso de inglés maestro. Parafrasear y escribir parches son etapas necesarias del desarrollo de la capacidad de expresar ideas propias; además, adoptar una estrategia de uso de cierta cantidad de plagio puede ser exitoso para mejorar el conocimiento de un idioma extranjero. Los participantes del estudio fueron 111 estudiantes que realizaron sus cursos de maestría en 3 universidades líderes en Moscú, Rusia.